Comparison of newly formed microcracks after instrumentation using Protaper Next, Reciproc and Self-Adjusting File systems - Fatih Çakıcı; Elif Bahar Çakıcı; Burak Sadık; Ali Keleş; Funda Fundaoglu Küçükekenci (Istanbul University, 2019)
Purpose The purpose of the present study is to assess the rate of newly formed microcracks comparatively during root canal instrumentation by using ProTaper Next, Reciproc, and Self-Adjusting File systems using micro-computed tomography. Subjects and Methods Thirty mesial roots of mandibular molars were randomly assigned to 3 experimental groups (n = 10) as follows, ProTaper Next, Reciproc and Self-Adjusting File system. Preoperative and postoperative scans were obtained at the isotropic resolution of 13.68 μm. Cross-section images were examined to identify the presence of newly formed dentinal microcracks. Results The Self-Adjusting File and Reciproc systems caused a higher rate of new microcrack formation than the ProTaper Next group (p < 0.001). There were also significant differences in the new microcrack formation between Reciproc and Self-Adjusting File groups (p < 0.001). Conclusion Reciproc and Self-Adjusting File systems caused a higher rate of newly formed microcraks compared to ProTaper Next system.